2021
DOI: 10.1038/s41598-021-82838-5
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycemia and the risk of end stage renal disease in type 2 diabetes

Abstract: We investigated the association between the incidence of severe hypoglycemia and the risk of end-stage renal disease (ESRD) in patients with type 2 diabetes. Baseline and follow-up data for 988,333 participants with type 2 diabetes were retrieved from the National Health Insurance System database. The number of severe hypoglycemia episodes experienced from 2007 to 2009 was determined. The primary outcome was the development of ESRD after the baseline evaluation. Participants were followed from the baseline unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Our data suggest that, although patients may have a low BMI or do not smoke, they should require more medical attention for renal complications if they develop T2DM at an early age. Our data also suggest that patients with YOD who have concomitant hypertension or dyslipidemia should be aware of the potential development of nephropathy 30 .…”
Section: Discussionmentioning
confidence: 54%
“…Our data suggest that, although patients may have a low BMI or do not smoke, they should require more medical attention for renal complications if they develop T2DM at an early age. Our data also suggest that patients with YOD who have concomitant hypertension or dyslipidemia should be aware of the potential development of nephropathy 30 .…”
Section: Discussionmentioning
confidence: 54%
“…Low blood glucose is known to be associated with increased mortality, CVD and ESRD in diabetes patients as well as the increased risk for the development of new-onset diabetes [ 30 ]. In a large nationwide T2DM cohort study, clinically significant hypoglycemia was associated with a 1.8 and 1.5-fold greater risk of developing incident CKD and all-cause mortality [ 31 , 32 ], and post hoc analysis of Action in Diabetes and Vascular disease: PreterAx and DiamicroN Controlled Evaluation (ADVANCE) study showed that hypoglycemia was associated with increased risks of micro- and macro-vascular events [ 33 ]. However, hypoglycemia has not been well studied in the general population without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was newly diagnosed SH during the follow-up period. According to ICD-10 based diagnostic clinical codes for SH [ 17 20 ], postmenopausal women with T2DM who had any claims for E1163−, E1463–, E160–, E161–, and E162–from inpatient, outpatient, or emergency room since the date of the health examination were classified as having experienced SH episodes. Only the first SH episodes within the observation period were included.…”
Section: Methodsmentioning
confidence: 99%